2022
DOI: 10.1111/jbfa.12669
|View full text |Cite
|
Sign up to set email alerts
|

Environmental reputation and bank liquidity: Evidence from climate transition

Abstract: This study empirically investigates how a bank's nonfinancial signals of environmental reputation affect its deposits and credit provision in US counties with severe climate transition risks. We find that banks with higher reputational risks associated with environmental issues tend to experience declining deposits in counties exposed to severe climate change risks. Banks with a poor environmental reputation also reduce mortgage origination in such counties and diminish liquidity creation if they have high dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 99 publications
0
0
0
Order By: Relevance
“…In a recent paper, Choi et al (2023) affirm that a bank's reputation concerning environmental, social and governance (ESG) practices significantly influences bank liquidity in regions sensitive to climate change by demonstrating not also the strong relationship that exists between reputation and performance but also the growing role of sustainability considerations. Similarly, and Galletta and Mazzu' (2023) present evidence showcasing the significance of adopting risk management strategies and banking policies aligned with ESG principles and sustainability frameworks.…”
Section: Cluster 2 (Green Network): Reputational Risk In Financial In...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper, Choi et al (2023) affirm that a bank's reputation concerning environmental, social and governance (ESG) practices significantly influences bank liquidity in regions sensitive to climate change by demonstrating not also the strong relationship that exists between reputation and performance but also the growing role of sustainability considerations. Similarly, and Galletta and Mazzu' (2023) present evidence showcasing the significance of adopting risk management strategies and banking policies aligned with ESG principles and sustainability frameworks.…”
Section: Cluster 2 (Green Network): Reputational Risk In Financial In...mentioning
confidence: 99%
“…In a recent paper, Choi et al . (2023) affirm that a bank’s reputation concerning environmental, social and governance (ESG) practices significantly influences bank liquidity in regions sensitive to climate change by demonstrating not also the strong relationship that exists between reputation and performance but also the growing role of sustainability considerations.…”
Section: Cluster Analysismentioning
confidence: 99%
“…Companies with high liquidity have more resources to improve their environmental performance than those with weak liquidity. Based on the research conducted by (Choi et al, 2023;Farhan, Almaqtari, Hazaea & Al-ahdal, 2023;Farlinno & Bernawati, 2020), it has been determined that there exists a favorable correlation between a company's liquidity and its ability to invest more resources towards sustainability endeavors regarding environmental concerns, social issues, and employee compensation. Therefore, this study postulates the following hypothesis:…”
Section: Liquidity and Environmental Performancementioning
confidence: 99%
“…However, research (Salama, 2005) found profitability does not have a significant effect on environmental performance. Other studies indicate environmental performance is also affected by liquidity (Choi, Gam & Shin, 2023;Earnhart & Lizal, 2006). According to (Acero & Alcalde, 2020), a high degree of liquidity demonstrates how well businesses use their working capital.…”
Section: Introductionmentioning
confidence: 99%